Multispectral flow cytometry: The consequences of increased light collection. Issue 7 (13th June 2016) - Feher, Kristen; von Volkmann, Konrad; Kirsch, Jenny; Radbruch, Andreas; Popien, Jan; Kaiser, Toralf
Abstract: In recent years, multispectral flow cytometry systems have come to attention. They differ from conventional flow cytometers in two key ways: a multispectral flow cytometer collects the full spectral information at the single cell level and the detector configuration is fixed and not explicitly tuned to a particular staining panel. This brings about clear hardware advantages, as a closed system should be highly stable, and ease‐of‐use should be improved if used in conjunction with custom unmixing software. An open question remains: what are the benefits of multispectral over conventional flow cytometry in terms of sensitivity and resolution? To probe this, we use Q (detection efficiency) and B (background) values and develop a novel "multivariate population overlap factor" to characterize the cytometer performance. To verify the usefulness of our factor, we perform representative experiments and compare our overlap factor to Q and B . Finally, we conclude that the increased light collection of multispectral flow cytometry does indeed lead to increased sensitivity, an improved detection limit, and a higher resolution. © 2016 International Society for Advancement of Cytometry